Theoretical and Experimental Investigation of the Dynamic Behaviour of Centrifugal Fans - G. Mariaux; Y. Gervais; L. Crespeau (International Journal of Rotating Machinery)
In this paper, a theoretical model is proposed to investigate the centrifugal fans' transient behaviour in response to sudden imposed changes in pressure or flow rate. We are especially interested in the dissipative or creative energy transient behaviour of the fans located in actual aeraulic networks.